Crude pectinase parameter optimization for enhancing bael juice clarification (Indian Journal of Arid Horticulture, 2025)
This study investigates the optimization of crude pectinase concentration for  clarifying bael juice, which contains fibrous pulp that limits juice recovery. The  effects of different pectinase concentrations, incubation times, and temperatures on  juice yield and turbidity were analyzed. The results showed that a 3% crude pectinase  concentration, incubated for 60 minutes at 45°C, produced the highest juice yield  (67.8%) and the lowest turbidity (568 NTU). The study underscores that the optimal  conditions for maximizing juice yield while minimizing turbidity involve a careful  balance of enzyme concentration and incubation parameters.
Keywords: Bael; pectinase; clarification; yield; turbidity